Antifungal Activity of Ethanol Extract from Sungkai Leaves (Peronema canescens jack.) Againts Candida albicans: An in Vitro Study - Royza, Avip; Alhawaris, Alhawaris; Masyhudi, Masyhudi (Cakradonya Dental Journal, 2025)
Oral candidiasis is a disease that affects the tongue and oral mucosa and is caused by the growth of the fungus Candida albicans. Secondary metabolites found in ethanol extracts of Sungkai leaves (Peronema canescens Jack.) have been shown to inhibit fungal growth. The purpose of stude was to test the antifungal activity of an ethanol extract of Sungkai leaves on C. albicans growth in vitro. The study used the disc diffusion research design and a post-testonly control group design. C. albicans was cultured on Sabouraud Dextrose Agar (SDA) medium and treated with ethanol extracts of Sungkai leaves at concentration of 0.02, 0.04, 0.08, 0.16, and 0.32 g/mL. Ketoconazole at 0.02g/mL was used as a positive control, and 10% dimethyl sulfoxide (DMSO) used as a negative control. The process is repeated five times. The results showed that the ethanol extract of Sungkai leaves did not have antifungal activity against the growth of C. albicans which was indicated by the absence of an inhibition zone around the disc paper on the SDA media used. The conclusion was the ethanol extract of Sungkai leaves did not show antifungal activity against the growth of C. albicans fungus.